Incidence, Clinical Features, Management, and Prevention of Herpes Zoster in Patients Receiving Antitumor Necrosis Factor Therapy: A Clinical Review. Issue 3 (May 2020) - Kim, Byung-Soo; Maverakis, Emanual; Alexanian, Clarie; Wang, Jenny Z.; Raychaudhuri, Siba P.
Tumor necrosis factor (TNF) inhibitors have been used as an excellent therapeutic option in a variety of chronic inflammatory conditions. However, a recognized significant adverse effect of TNF inhibitor therapy is the increased risk of infections. The influence of TNF inhibitors on the course of coexisting or newly developed viral infections has not been extensively investigated. Therefore, we reviewed the recent publications to highlight the incidence, clinical features, management, and prevention of herpes zoster in patients who are receiving TNF inhibitors.